The collected works of Eugene Paul Wigner - Wigner, Eugene Paul (Springer-Verlag, 1992)
Eugene Wigner is one of the very few scientists that may safely be describedas creators of 20th-century physics. This volume of his Collected Works is devoted to his contributions to nuclear energy. In his Introduction and Annotations A.M. Weinberg surveys Wigner's contributions to nuclear-reaction physics and nuclear engineering, at the same time giving a glimpse of the early history of nuclear-reactor technology. Wigner himself gave a lively and critical account, which is published in this volume for the first time. Furthermore the book contains forty-two reports and memoranda from 1941 to 1945 and twelve of Wigner's many patents relating to nuclear energy.